2010 IEEE 17Th International Conference on Industrial Engineering and Engineering Management 2010
DOI: 10.1109/icieem.2010.5645907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organizational justice over affective commitment and the role of marital status

Abstract: This study aims at exploring the effect of 'organizational justice' over 'affective commitment' and the role of marital status, if any, in the relationship. A total of 207 responses from 18 organizations are collected and analyzed. The study has found that 'procedural justice' has positive effect over 'affective commitment' but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The relationship between organizational justice and employee commitment has focused largely on the distributive and procedural components. Some authors have been unable to distinguish the effects of distributive and procedural justice on organizational commitment, especially on affective commitment (Chai-Amonphaisal and Ussahawanitchakit 2008; Klendauer and Deller 2009; Meyer et al 2002), but other empirical results have been mixed, as some research has supported procedural justice as the strongest predictor of affective commitment (Haque, Chowdhury, and Ali 2010; Harvey and Haines 2005; Lambert et al 2005), while other research has shown that distributive justice is the stronger predictor of affective commitment (Clay-Warner, Reynolds, and Roman 2005; Farmer, Beehr, and Love 2003; Schappe 1998). In any case, researchers have found support for procedural justice influencing the development of normative commitment (Cohen-Charash and Spector 2001; Jamaludin 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between organizational justice and employee commitment has focused largely on the distributive and procedural components. Some authors have been unable to distinguish the effects of distributive and procedural justice on organizational commitment, especially on affective commitment (Chai-Amonphaisal and Ussahawanitchakit 2008; Klendauer and Deller 2009; Meyer et al 2002), but other empirical results have been mixed, as some research has supported procedural justice as the strongest predictor of affective commitment (Haque, Chowdhury, and Ali 2010; Harvey and Haines 2005; Lambert et al 2005), while other research has shown that distributive justice is the stronger predictor of affective commitment (Clay-Warner, Reynolds, and Roman 2005; Farmer, Beehr, and Love 2003; Schappe 1998). In any case, researchers have found support for procedural justice influencing the development of normative commitment (Cohen-Charash and Spector 2001; Jamaludin 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, research is mixed as to the impact of the different components of organizational justice and job satisfaction on the three components of organizational commitment. Some authors state that procedural justice is a stronger predictor of affective commitment (Harvey and Haines 2005; Haque, Chowdhury, and Ali 2010; Lambert et al 2005), but others state that the stronger predictor is distributive justice (Clay-Warner, Reynolds, and Roman 2005; Farmer, Beehr, and Love 2003; Schappe 1998). When other components of commitment are considered, researchers have even discarded the relationships between some of the variables (Turgut, Tokmak, and Gucel 2012), and, moreover, the relationship between interactional justice and organizational commitment is controversial.…”
mentioning
confidence: 99%
“…Conducted in the recent past, it has been found that procedural justice influences affective organizational commitment positively (Appaw-Agbola et. al., 2021;Lambert et al, 2020;Nazir et al, 2019;Charbonneau and Wood, 2018;Haque et al, 2010). Thus, we propose: H1.…”
Section: Procedural Justice and Affective Commitmentmentioning
confidence: 93%
“…Yet, much prior work had focused on studying the three types of organizational commitment (affective, continues and normative) through only the influence of distributive and procedural forms, while other researchers were unable to differentiate the different strong influences of these forms on AOC (Chai-Amonphaisal and Ussahawanitchakit, 2008;Klendauer and Deller, 2009). Exiting debates among scholars around which DJ or PJ has stronger impact on AOC, some studies had highlighted that DJ has a higher impact on AOC (Clay-Warner, Reynolds, and Roman, 2005;Farmer et al, 2003), adding to the complexity, other studies revealed that PJ has a stronger effect on AOC (Haque, Chowdhury, and Ali, 2010;Harvey and Haines Iii, 2005; López-Cabarcos, Machado-Lopes-Sampaio-de Pinho, and Vázquez-Rodríguez, 2015b). According to the researchers' knowledge, no studies have investigated the different strong effect of the three forms organizational justice on AOC especially in the hospitality context.…”
mentioning
confidence: 99%